2015
DOI: 10.1002/dvdy.24263
|View full text |Cite
|
Sign up to set email alerts
|

Critical role of YY1 in cardiac morphogenesis

Abstract: Background: Yin Yang 1 (YY1), the only DNA binding polycomb group protein, was reported to regulate cardiomyocyte differentiation during early cardiac mesoderm development. However, whether it contributes to cardiac morphogenesis at later developmental stage(s) during embryogenesis is unknown. Results: We excised YY1 in murine hearts during embryogenesis using two temporal-spatially controlled cre activation approaches, and revealed critical roles of YY1 in cardiac structural formation. Alpha-myosin heavy chai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
25
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 52 publications
3
25
0
Order By: Relevance
“…Recent studies showed binding of YY1 to the promoters of highly expressed ribosomal proteins and the nuclear encoded mitochondrial membrane, enzymes, and ribosomal proteins (35) and highlighted the importance of YY1 in cardiomyocyte differentiation and heart morphogenesis (30,31). Notably, cardiacspecific ablation of Yy1 causes severe abnormalities in the heart, indicating that YY2 in the heart does not compensate for YY1 deletion (31). Comparison of YY2 and YY1 ChIP-Seq data ( Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies showed binding of YY1 to the promoters of highly expressed ribosomal proteins and the nuclear encoded mitochondrial membrane, enzymes, and ribosomal proteins (35) and highlighted the importance of YY1 in cardiomyocyte differentiation and heart morphogenesis (30,31). Notably, cardiacspecific ablation of Yy1 causes severe abnormalities in the heart, indicating that YY2 in the heart does not compensate for YY1 deletion (31). Comparison of YY2 and YY1 ChIP-Seq data ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies showing that YY1 directly regulates Nkx2.5 expression and promotes cardiogenesis uncovered a novel function for YY1 in cardiomyocyte differentiation and cardiac morphogenesis (30,31). To examine the effect of YY2 on mESC differentiation toward cardiovascular lineages, EBs derived from dox-YY2 mESCs were exposed to doxycycline.…”
Section: Ablation Of Eif4ebp1 and Eif4ebp2mentioning
confidence: 99%
“…In our previous work, we identified several YY1 downstream targets, and Mesp1 was one of them and was the most significantly affected (Beketaev et al, ). In the present study, we aimed to further understand how the Mesp1 expression is mediated by working on the cis‐regulatory sequences of Mesp1 gene that was fused to different reporters.…”
Section: Introductionmentioning
confidence: 95%
“…Many PcG null mutations of one of the orthologs in mice can survive to later embryonic stages; some of them are even viable, showing very mild phenotypes [94] (see Tables 2-5). Furthermore, analyzing the mouse phenotypes of late lethal PcG mutations, it became obvious that although these factors play profound role in homeotic regulation [158,159], their epigenetic repressor functions are also important in hematopoiesis [160][161][162][163] (reviewed in [164] and [165]), neuronal [154,166] (reviewed in [167]) cardiac [168][169][170] and skeletal muscle differentiation [171], as well as in the maintenance of germ cell fate [172][173][174][175].…”
Section: Mammalian Pcg Gene Functions: Parallels and Differences Betwmentioning
confidence: 99%
“…Mesp1-cre mediated knockout of Yy1 (Mesp1-YY1) at early developmental stage (at E6.5) resulted in abolished cardiac lineage formation and YY1 together with GATA4 transcriptionally activates early cardiac enhancer, Nkx2.5 [263]. A latest study found that MHC-cre mediated Yy1 null mice (MHC-YY1) displayed congenital heart defects with defective cardiomyocyte proliferation and increased apoptosis, while Nkx2.5-cre mediated Yy1 null mouse embryos (Nkx2.5-YY1) showed hypoplastic endocardial cushions in atrioventricular canal and outflow tract and died around E13.5 [170]. They also identified downstream targets of YY1 that are cardiac morphogenesis regulators (Mesp1, Cited1, eHAND and Dll) [170].…”
Section: The Function Of Yy1mentioning
confidence: 99%